Assessment of a portable prothrombin time analyzer (CoaguChek‐XS) in dogs. (15th July 2014) - Kelmer, Efrat; Segev, Gilad; Codner, Carolina; Bruchim, Yaron; Klainbart, Sigal; Aroch, Itamar
Abstract Objectives To assess the performance of a portable prothrombin time (PT) analyzer (CoaguChek‐XS) in dogs. Animals Ninety‐seven dogs composed of 20 healthy dogs, 45 ill dogs, and 32 ill dogs with altered coagulation. Procedures Samples were concurrently obtained and PT was measured using the CoaguChek‐XS and an automated coagulation analyzer. Agreement between methods was assessed using Spearman's correlation and Bland–Altman analysis. Results The reference interval for PT using the CoaguChek‐XS was 9.6–11.5 s. The CoaguChek‐XS was easy to use, required a small volume of whole blood, and gave results within 1 min. The mean difference in PT between the 2 methods was 2.58 s (SD 3.10), and 94% of the samples fell within limits of agreement. The correlation was moderate, but significant (r = 0.35, P < 0.001). Sensitivity and specificity of the CoaguCheck‐XS PT compared to analyzer PT were 92% and 56%, respectively, and increased to 95% and 77% on intent to treat basis. The coefficient of variance was 0.72%. The CoaguChek‐XS identified all 8 dogs with anticoagulant rodenticide intoxication, although a discrepancy was noted from the analyzer results. In anemic dogs (PCV≤25%), the CoaguChek‐XS did not display accurate results. Conclusions The CoaguChek‐XS is a simple, user‐friendly, highly precise PT analyzer. Results had moderate correlation and good agreement with a standard method. It can be used reliably for screening dogs when the PT is normal. However, when the CoaguChek‐XS PT is prolonged or when the PCV is ≤25%, results should be confirmed using a standard method.